Internet of things - enabled stress surveillance when pandemic lockdown: revolutionizing resilience - Hasanudin, Afif Hakim; Othman, Mohd Azlishah; Azwan, Alya Azwa; Mohd Roki, Abdul Aziz Faqruldin; Ismail, Shahira; Nugraha, Y.T.; Suhaimi, S.; Hassan, N.M. (2023)
The COVID-19 pandemic and subsequent lockdowns have had a negative impact on worldwide mental health, resulting in elevated stress levels. This stress affects not just people but also others close to them. However, stress can be difficult to identify and frequently goes unrecognised, posing a serious threat to one's health. This research seeks to address this issue by developing a cutting-edge stress monitoring system. The gadget, dubbed 'Stress Measure,' uses IoT technology to monitor heart rate levels in real-time and offer a full picture of stress levels. The ultimate purpose of this initiative is to empower people to take charge of their mental health during these unusual times, by giving them with the skills they need to manage stress and preserve their well-being throughout the pandemic lockdown.